Rhizosphere Soil Bacterial Communities of Continuous Cropping-Tolerant and Sensitive Soybean Genotypes Respond Differently to Long-Term Continuous Cropping in Mollisols - Yuan, Ming; Yu, Taobing; Shi, Qihan; Han, Dongwei; Yu, Kanchao; Wang, Lianxia; Wang, Shurong; Xiang, Hao; Wen, Ronghui; Nian, Hai; Lian, Tengxiang (Frontiers in Microbiology, 2021)
The continuous planting of soybeans leads to soil acidification, aggravation of soil-borne diseases, reduction of soil enzyme activity and accumulation of toxins in the soil. Microorganisms in the rhizosphere play a very important role in maintaining the sustainability of the soil ecosystem and plant health. In this study, two soybean genotypes, one bred for continuous cropping and the other not, were grown in a Mollisol in northeast China under continuous cropping for 7 and 36 years in comparison to soybean-maize rotation, and microbial communities in the rhizosphere composition wasassessed using high-throughput sequencing technology. The results showed that short- or long-term continuous cropping had no significant effect on the rhizosphere soil bacterial alpha diversity. Short-term continuous planting increased the number of cyst nematodes, while long-term continuous planting reduced these numbers. There were less cyst nematodes in the rhizosphere of the tolerant genotypes than sensitive genotypes. In addition, continuous cropping significantly increased the potential beneficial bacterial populations, such as Pseudoxanthomonas, Nitrospira and Streptomyces compared to rotation and short-term continuous cropping, suggesting that long-term continuous cropping of soybean shifts the microbial community towards a healthy crop rotation system. Soybean genotypes that are tolerant to soybean might recruit some microorganisms that enhance the resistance of soybeans to long-term continuous cropping. Moreover, the network of the two genotypes responded differently to continuous cropping. The tolerant genotype responded positively to continuous cropping, while for the sensitive genotype, Topology analyses on the instability of microbial community in the rhizosphere suggested that short periods of continuous planting can have a detrimental effect on microbial community stability, although this effect could be alleviated with increasing periods of continuous planting.